A Comparison of the Impact of Artificial Intelligence on Digital Laws in the Kingdom of Saudi Arabia and the United Arab Emirates - Ismail Khaled Salem (International Journal of Law Research and Studies, 2025)
This study aims to compare the impact of artificial intelligence on digital laws in Saudi Arabia and the United Arab Emirates, using a comparative analytical approach based on quantitative and qualitative data. The data was analyzed using advanced statistical tools and expert interviews, providing a deep understanding of the differences and similarities between the two countries in their approaches to integrating AI into their legal frameworks. The results showed that the UAE has made faster progress in integrating AI into legal systems through digital initiatives and flexible regulations, while Saudi Arabia is witnessing significant progress but is still in the regulatory development stages. The study also highlighted the urgent need to update legislation, train personnel, protect personal data, and provide a flexible and transparent legal environment capable of accommodating digital transformations. By providing a set of strategic recommendations, this study contributes to establishing a strong legal foundation that supports digital transformation in the Gulf countries, in line with societal values and international best practices.